An Analysis of Factors Affecting Parental Behavior in Providing Early Age Sex Education - Kartika Adyani; Machfudloh Machfudloh; Sunarto Sunarto (JURNAL KEBIDANAN, 2021)
Sexual violence against children is increasing. It makes the urgency of providing sex education for children fromtheir early ages. However,many parents still consider it taboo for early childhood sex education,so they neglect it. This research aimedto analyze the factors that affectparental behavior inproviding sex education to early childhood. This researchwasa Cross-Sectional Study involving 239 parents who have children under the age of 6 years. The data analysis was performed using Chi-square test. The results of this study indicated that the factorsrelatingto the behavior of providing early sex education by parents areknowledge (p=0.342), attitude (p=0.581), and role (p=0.163). Less knowledgeable parents have a 1.35 times risk of not providing early sex education. Concurrently, parents who are not supportive have a 1.18 times risk of not providing early sex education.When the dominant role is the mother, the risk is 1.83 times not to provide sex education for early childhood. Less knowledgeable parents have an unsupportive attitude, and the dominant role is that mothers tend not to provide sex education to early childhood. Parents can collaborateto improve knowledge about early childhood sex education and deliverit to children from their early ages